Imported inputs and invoicing currency choice: theory and evidence from UK transaction data - Chung, Wanyu (Elsevier, 2016)
A significant proportion of international trade is in intermediate goods. This paper considers theoretically and empirically how exporters' dependence on imported inputs affects their choice of invoicing currency. The model predicts that exporters that depend more on foreign currency-denominated inputs are less likely to price in their home currency. I test this and other theoretical results using a novel dataset that covers UK trade transactions with non-EU countries. I find considerable support for the model's predictions. A 10 percentage point higher share of foreign currency-denominated inputs is associated with a 20 percentage point higher probability of pricing in the same foreign currency relative to the producer's currency.